Low Back Pain and Associated Factors among Workers in The Blacksmithing Industry in Java, Indonesia - Diana Lutvia; Retno Wibawanti; Ahmad Fuady; Muhammad Ilyas; Dewi Sumaryani Soemarko (ILUNI MKK FKUI and PRODI MKK FKUI, 2026)
Background: Low back pain (LBP) is a common musculoskeletal disorder among informal sector workers, including blacksmiths. particularly because of non-ergonomic work positions.Objective: This study aims to identify the prevalence of low back pain (LBP) and its associated characteristics among blacksmith workers in Mekarmaju Village, Bandung Regency.Methods: A cross-sectional study was carried out among 105 blacksmiths with interview, the Bodymap Discomfort questionnaire, the Visual Analogue Scale (VAS), physical examination, and measurement of trunk flexion angle using APECS version 8.05.07. In this study, LBP among blacksmith workers was characterized as chronic non-specific low back pain.Results: LBP prevalence among blacksmiths was 58.1%. Factors significantly associated with LBP included forward-bending posture (p=0.034; aOR 3.7; 95% CI 1.1–12.5), static sitting posture for ≥4 hours (p=0.009; aOR 3.6; 95% CI 1.4–9.4), rest duration <0.5 hours (p=0.006; aOR 7.9; 95% CI 1.8–35.3), and age ≥35 years (p=0.006; aOR 4.6; 95% CI 1.6–13.6). Other occupational and individual factors didn’t have a significant correlation with LBP.Conclusion: These results indicate the necessity for immediate ergonomic interventions and health assessments at the beginning of employment for preventing LBP among informal sector workers.